UJI ZPT HANTU TERHADAP PERTUMBUHAN DAN PRODUKSI SELADA MERAH (Lactuca sativa) - Seprita Lidar; Enny Mutryarny (Jurnal Ilmiah Pertanian)
Lettuce plants is one of the vegetables that have commercial value and good prospects for development, because demand for lettuce plants continues to increase in line with population growth and awareness of nutritional needs and the development of such culinary business. Red lettuce new red fire red to black curly leaves, the red if given full sun. This type of lettuce is not widely grown in Riau, when environmental conditions allow, the problem is the type of Ultisol, then to overcome it is to the development of good farming such as the provision of plant growth regulator (PGR) Hantu. Hantu PGR containing gibberellic acid, Indol Acetic Acid, Kinetin and Zeatin. The research objective was to determine the effect and get the best Hantu PGR concentration on the growth and production of red lettuce. Research conducted experiments with completely randomized design with 5 level of treatment that is without giving PGR Hantu (H0), the provision of 1 ml / l of water (H1), administration of 2 ml / l of water (H2), giving 3 ml / l water (H3) and the provision of 4 ml / l of water (H4) to four (4) replicates. Data were analyzed by analysis of variance followed by a further test DMRT level of 5%. The results showed that the Hantu PGR can promote the growth and production of red lettuce plants, with the best concentration was 2 ml / l of water.